The Development of care model for Patients with Chronic Kidney Disease at Phayao hospital and Network - Kaewboonsert, Donkum; Chuayunan, Niphitphon; khamnuan3, Patcharin (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
This research and development aim to develop of care model for patients with chronic kidney disease and study the effects of using the model of care for patients with chronic kidney disease, Phayao Hospital and network. The sample includes nurses and health teams working in chronic kidney clinics at Phayao Hospital and a network, of 16 people, and patients with chronic kidney disease receive services at the chronic kidney clinic from July to September 2023, 57 people. The tools used to conduct the research include models of care for patients with chronic kidney disease at Phayao Hospital and network using the LINE OA application account named “Yu-kạb-hmo-tai” (Staying with kidney doctor). Data collection tools include patients with chronic kidney disease questionnaires and questionnaires for nurses and health teams. Data were analyzed data using descriptive statistics, including frequency, percentage, mean, standard deviation, and inferential statistics, including the Paired t-test with a statistical significance level of 0.05. The research findings indicate that the model of care for patients with chronic kidney disease Phayao Hospital and network using the LINE OA application “Yu-kạb-hmo-tai” operates as the model of education and consultation through the LINE application account that includes infographics and online videos about chronic kidney disease, medication guidelines, dietary considerations, exercise regimens, mood management strategies for CKD patients, factors contributing to kidney degeneration, and measures for preventing and slowing down the progression of kidney degeneration, etc. The results of the model application showed a statistically significant increase in knowledge and behavior in self-care after the use of the model (p < 0.05). The estimated Glomerular Filtration Rate (eGFR) has increased statistically significantly. (p < 0.05). The highest level of satisfaction with the model (Mean 4.21). Nurses and health teams were also most satisfied with the model. (Mean 4.24)